2014
DOI: 10.1177/0969141314534406
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological differences between interval and screen-detected breast cancers diagnosed within a screening programme in Northern Portugal

Abstract: Objective: To evaluate clinicopathological differences between screen-detected (SD) and interval (IC) breast cancers diagnosed in women enrolled in an organized breast screening programme in [2000][2001][2002][2003][2004][2005][2006][2007]. Setting: Breast Cancer Screening Programme of the north region of Portugal. Methods: Using data from the screening programme and from the population-based North Region Cancer Registry, SD and IC were identified. Information on screening history, age, date of diagnosis, tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Mirroring reports on interval cancers among the general breast cancer population, we found that interval cancers had higher-risk features. [22,13,16,[23][24][25]20,21] The interval cancers in this population were all invasive, larger, and more likely to be node positive at presentation compared to screen-detected tumors. While the literature demonstrates that interval cancers in the general population are more likely to be triple negative or estrogen receptor negative/ progesterone negative/HER2 positive [12,13,16,25,20], we found no difference in receptor status between interval and screen-detected tumors.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Mirroring reports on interval cancers among the general breast cancer population, we found that interval cancers had higher-risk features. [22,13,16,[23][24][25]20,21] The interval cancers in this population were all invasive, larger, and more likely to be node positive at presentation compared to screen-detected tumors. While the literature demonstrates that interval cancers in the general population are more likely to be triple negative or estrogen receptor negative/ progesterone negative/HER2 positive [12,13,16,25,20], we found no difference in receptor status between interval and screen-detected tumors.…”
Section: Discussionmentioning
confidence: 81%
“…Demographics associated with interval cancer development among this cohort of BRCA mutation carriers included younger age and Black race, factors reported to be associated with interval cancers among the general population. [11,13,16,23,20] Women with interval cancers were less likely to have undergone a BSO, which may be a reflection of the younger age of this cohort. A lower BMI was also significantly associated with interval cancers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 3 Many studies have found that screen-detected cancers have more favorable clinicopathologic factors and prognosis that might be associated with a different tumor biology compared with interval cancers. 8 - 16 , 25 - 36 Patients with a screen-detected cancer were more likely to have a low- or even an ultra–low-risk tumor compared with interval cancers assessed by the 70-gene signature. 25 , 26 Specific copy number imbalances were also noted in screen-detected breast cancers associated with more favorable, indolent tumor genotypes and might contribute to the survival advantage associated with screening.…”
Section: Discussionmentioning
confidence: 99%